Contrasting Effects of Systemic Monocyte/Macrophage and CD4+ T Cell Depletion in a Reversible Ureteral Obstruction Mouse Model of Chronic Kidney Disease - Lee D. Chaves; Liby Mathew; Mohammed Shakaib; Anthony Chang; Richard J. Quigg; Tipu S. Puri (Clinical and Developmental Immunology)
Using a reversible UUO model (rUUO), we have demonstrated that C57BL/6 mice are susceptible to development of CKD after obstruction-mediated kidney injury while BALB/c mice are resistant. We hypothesized that selective systemic depletion of subpopulations of inflammatory cells during injury or repair might alter the development of CKD. To investigate the impact of modification of Th-lymphocytes or macrophage responses on development of CKD after rUUO, we used an anti-CD4 antibody (GK1.5) or liposomal clodronate to systemically deplete CD4+ T cells or monocyte/macrophages, respectively, prior to and throughout the rUUO protocol. Flow cytometry and immunohistochemistry confirmed depletion of target cell populations. C57BL/6 mice treated with the GK1.5 antibody to deplete CD4+ T cells had higher BUN levels and delayed recovery from rUUO. Treatment of C57BL/6 mice with liposomal clodronate to deplete monocyte/macrophages led to a relative protection from CKD as assessed by BUN values. Our results demonstrate that modulation of the inflammatory response during injury and repair altered the susceptibility of C57BL/6 mice to development of CKD in our rUUO model.